Oxidation of dietary linoleate occurs to a greater extent than dietary palmitate in vivo in humans. Issue 3 (March 2021) - Parry, Siôn A.; Rosqvist, Fredrik; Cornfield, Thomas; Barrett, Amy; Hodson, Leanne
Summary: Background: It has been suggested that dietary polyunsaturated fatty acids (PUFA) are partitioned into oxidation pathways to a greater extent than dietary saturated fatty acids (SFA). Whilst this has been demonstrated in animal models, evidence in humans is lacking. The potential divergence in the metabolic fate of these dietary fatty acids (FA) may explain some of the reported differences in ectopic fat deposition with SFA and PUFA enriched diets. Aims: To compare whole-body oxidation of dietary palmitate and linoleate after consumption of a single test meal. Methods: In a randomized, crossover design 24 healthy volunteers (12 males and 12 females, matched for age and BMI) underwent two study days separated by 2-week washout period. During each study day participants consumed a standardized test meal which contained [U 13 C]palmitate or [U 13 C]linoleate. Blood and breath samples were collected over the 6 h postprandial period and the 13 C enrichment in breath CO2 samples and plasma lipid fractions was determined. Results: Appearance of 13 C in expired CO2 was significantly ( p < 0.05) increased after consumption of the meal containing [U 13 C]linoleate compared to the meal containing [U 13 C]palmitate. The recovery of tracer was 8.9 ± 1.2% [U 13 C]linoleate vs . 5.6 ± 0.4% [U 13 C]palmitate ( p < 0.05). The incorporation of 13 C from [U 13 C]palmitate was greater in plasma triacylglycerol and non-esterified fatty acids than [U 13 C]linoleate, whereas the incorporation of 13 C from [U 13 C]linoleate was greater than [U 13 C]palmitate in plasma phospholipids. Although 13 CO2 was significantly ( p < 0.05) higher in females compared to males after consumption of [U 13 C]palmitate, there was no difference in 13 CO2 between sexes after consumption of [U 13 C]linoleate. Conclusions: We demonstrate that whole-body oxidation of dietary linoleate is comparatively higher than that of dietary palmitate in humans following consumption of a single mixed-test meal. We found indications of sexual dimorphism for dietary palmitate but not dietary linoleate. Study registration: http://www.clinicaltrials.org/ ID number NCT03587753 .